IDENTIFIKASI PERILAKU DEFORMASI VERTIKAL BERDASARKAN HASIL PEMANTAUAN MULTILAYER SETTLEMENT SAAT PELAKSANAAN TIMBUNAN BENDUNGAN AMERORO - Alfian Arbie Simbolon; Sri Prabandiyani Retno Wardani; Suharyanto Suharyanto (Racic : Rab Construction Research, 2024)
The Ameroro Dam, located in Southeast Sulawesi, was built by the Ministry of Public Works and Public Housing and is currently still in the process of filling. Dam deformation actually started to occur during the dam construction process and then continued during the dam's operational period after construction was completed. Therefore, it is very important to observe and analyze the deformation of the dam body since the construction period to avoid dam failure in the future. This research aims to identify the vertical internal deformation behavior of the Ameroro Dam based on data from Multilayer Settlement monitoring results. The identification is intended to assess the normal or abnormal behavior of the core zone of the dam embankment using reading data from the Multilayer Settlement instrument installed at the Ameroro Dam to determine its deformation behavior based on empirical references. The reading graph of the Multilayer Settlement monitoring results shows that the bottom magnetic plate of IMS 1-8 has experienced a stagnant decline at the embankment elevation of +88.50 m so that it is predicted that at the next embankment increase the deformation will be stable. The normal limit referred to is when the height of the embankment is less than 50 m, the total settlement is generally in the order of less than 1% to 2.5%. From the results of the analysis, the settlement value at the core of the Ameroro Dam that occurred was still within normal limits.